On the mechanism and applications of on-line sample concentration techniques in capillary electrophoresis - AGNES, ARANAS (Archīum Ateneo, 2012)
Efforts to overcome the low concentration sensitivity of Capillary Electrophoresis (CE) have continued to be an important area of research in analytical chemistry. This dissertation deals with the review, application and development of on line sample concentration in CE. On-line sample concentration is one of the approaches and now an important area of research to improve the poor detection sensitivity of CE. This approach only takes advantage of the small sample volume requirement in CE and is performed by injecting a larger volume of sample solution and then focusing the analytes in that long sample zone inside the capillary into a narrow band before separation. Since a large amount of analytes are introduced, an enhancement in the signals is expected at the end, thereby increasing the sensitivity of CE...